2013
DOI: 10.1097/adt.0b013e31826ac408
|View full text |Cite
|
Sign up to set email alerts
|

An Interpersonal Model of Addiction Relapse

Abstract: In this article, we review the literature on interpersonal stress and rejection sensitivity and examine how these factors increase the risk of relapse in individuals with alcohol or drug dependence. We begin by considering the constructs of social pain and social threat, examining their evolutionary origins and their neuroanatomical, neuropsychological and neurophysiological dimensions. Together, these perspectives provide insight into the role of interpersonal stress as a powerful and oftentimes destructive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…These results corroborate prior research demonstrating that social context is an important aspect of SUDs (Galea et al, 2004; Leach & Kranzler, 2013). Previous work has focused primarily on the role of social support networks and peer influences on treatment outcomes in mutual-help groups (Groh et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results corroborate prior research demonstrating that social context is an important aspect of SUDs (Galea et al, 2004; Leach & Kranzler, 2013). Previous work has focused primarily on the role of social support networks and peer influences on treatment outcomes in mutual-help groups (Groh et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…SUDs often develop in the context of poor relationships with family (Bahr, Marcos, & Maughan, 1995; Galea et al, 2004; Stone, Becker, Huber, & Catalano, 2012) as well as associations with substance-using peers. Moreover, interpersonal stress may precipitate relapse (Leach & Kranzler, 2013). Interpersonal relationships are also a primary component of successful SUD interventions (Moos, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lack of social support has been associated with poorer treatment outcomes ( 136 ), and increases the chance of relapse ( 137 ). For instance, interpersonal conflicts may result in increases in negative affect, which then leads an individual to engage in addictive behaviors as a means of coping ( 138 ). Enabling, that is, the well-intentioned but unhelpful behaviors of friends or family is another concept that has been shown to increase the use of addictive behaviors ( 139 ).…”
Section: Deficits In Social Supportmentioning
confidence: 99%
“…All the subjects were assessed on socio-demographic characteristics and history of substance abuse, and then subjected to Family Typology Scale, Family Interaction Scale, Presumptive Stressful Life Events Scale, Eyesenck"s Personality Questionnaire and Multidimensional Scale of Perceived Social Support. It was found that relapse was more in substance abusers of less than 30 years of age, those having lower educational and socio-economic status, unemployed, having family history of substance abuse and past history of crime [6] Matoo, et al conducted a study on psychosocial factors associated with relapse in men with alcohol and opiod dependence. They reported that patients who relapsed were significantly more likely (i) to have a positive history of substance use and higher number of previous relapses; (ii) to be using maladaptive coping strategies; (iii) to have been exposed to a higher number of high risk situations; and (iv) have experienced a higher number of undesirable life events.…”
Section: Literature Surveymentioning
confidence: 99%